Analysis of Employee Performance on Customer Satisfaction Levels in Motor Vehicle Washing Services at CV Tirta Mandiri, Nusaniwe District, Ambon City - Hayoto, Dewi Justia; Wairisal, Paulus Liberthy; Rehatta, Geradin (Universitas Pattimura, 2025)
This study aims to analyze the influence of employee performance on customer satisfaction in motor vehicle washing services at CV Tirta Mandiri, Nusaniwe District, Ambon City. Employee performance in this study encompasses various aspects, including punctuality, quality of washing results, as well as interaction and attitude towards consumers. The research method applied is a quantitative survey using questionnaires distributed to consumers as respondents. The data obtained were analyzed using simple linear regression to determine the relationship between employee performance and customer satisfaction. The results indicate that employee performance has a significant and positive effect on customer satisfaction levels. These findings suggest that the better the performance displayed by employees, the higher the satisfaction level perceived by customers. Moreover, aspects such as punctuality and the quality of washing results are crucial factors in determining customer satisfaction. This study highlights the importance of enhancing employee performance in vehicle washing services to improve the overall customer experience. In conclusion, improvements and training in both technical and communication skills for employees are highly recommended to support efforts in boosting customer loyalty and retention